Assessing nation state threats. Issue 9 (September 2017) - Condra, Jon
Abstract : Cyber-attacks by nation states are increasingly emerging from the shadows and garnering greater public awareness. Suspicions over meddling in elections have given rise to mounting political tensions and even led many to question the accuracy of election results. These issues are in turn creating widespread public concerns over the cyber activities and capabilities of nation states.